Cloning and expression of a Salmonella enteritidis fimbrin gene in Escherichia coli. - Feutrier, J (1988)
A gene bank of DNA from a human isolate of Salmonella enteritidis was constructed in the cosmid pHC79 in Escherichia coli HB101. Five clones containing 35- to 45-kilobase inserts of S. enteritidis DNA reacted in colony immunoblot assays with a polyclonal antiserum prepared against purified S. enteritidis fimbriae. Electron microscopy showed that none of the five fimbrin-producing clones produced fimbriae, yet radioimmunoprecipitation and sodium dodecyl sulfate-polyacrylamide gel electrophoresis located the 14,400-molecular-weight S. enteritidis in the outer membrane fraction of three of the clones and in the periplasmic fraction of all five clones. By using an oligonucleotide probe homologous to the 5' region of the fimbrin structural gene, the fimbrin gene was located on a 5.3-kilobase HindIII fragment. In vitro transcription-translation analysis verified that this HindIII fragment subcloned into plasmid pTZ18R produced unprocessed S. enteritidis fimbrin of molecular weight 16,400. Dot blot hybridization against a selection of strains of the family Enterobacteriaceae indicated a limited distribution of the S. enteritidis fimbrin gene.